Cone-Beam-CT Guided Adaptive Radiotherapy for Locally Advanced Non-small Cell Lung Cancer Enables Quality Assurance and Superior Sparing of Healthy Lung - Hoegen, Philipp; Lang, Clemens; Akbaba, Sati; Häring, Peter; Splinter, Mona; Miltner, Annette; Bachmann, Marion; Stahl-Arnsberger, Christiane; Brechter, Thomas; El Shafie, Rami A.; Weykamp, Fabian; König, Laila; et al. (Frontiers in Oncology, 2020)
Purpose: To evaluate the potential of cone-beam-CT (CB-CT) guided adaptive radiotherapy (ART) for locally advanced non-small cell lung cancer (NSCLC) for sparing of surrounding organs-at-risk (OAR). Materials and Methods: In 10 patients with locally advanced NSCLC, daily CB-CT imaging was acquired during radio- (n=4) or radiochemotherapy (n=6) for simulation of ART. Patients were treated with conventionally fractionated intensity-modulated radiotherapy (IMRT) with total doses of 60-66 Gy (pPlan) (311 fraction CB-CTs). OAR were segmented on every daily CB-CT and the tumor volumes were modified weekly depending on tumor changes. Doses actually delivered were recalculated on daily images (dPlan), and voxel-wise dose accumulation was performed using a deformable registration algorithm. For simulation of ART, treatment plans were adapted using the new contours and re-optimized weekly (aPlan). Results: CB-CT showed continuous tumor regression of 1.1±0.4% per day, leading to a residual gross tumor volume (GTV) of 65.3±13.4% after 6 weeks of radiotherapy (p=0.005). Corresponding PTVs decreased to 83.7±7.8% (p=0.005). In the actually delivered plans (dPlan), both conformity (p=0.005) and homogeneity (p=0.059) indices were impaired compared to the initial plans (pPlan). This resulted in higher actual lung doses than planned: V20Gy was 34.6±6.8% instead of 32.8±4.9% (p=0.066), mean lung dose was 19.0±3.1 Gy instead of 17.9±2.5 Gy (p=0.013). The generalized equivalent uniform dose (gEUD) of the lung was 18.9±3.1 Gy instead of 17.8±2.5 Gy (p=0.013), leading to an increased lung normal tissue complication probability (NTCP) of 15.2±13.9% instead of 9.6±7.3% (p=0.017). Weekly plan adaptation enabled decreased lung V20Gy of 31.6±6.2% (-3.0%, p=0.007), decreased mean lung dose of 17.7±2.9 Gy (-1.3 Gy, p=0.005) and decreased lung gEUD of 17.6±2.9 Gy (-1.3 Gy, p=0.005). Thus, resulting lung NTCP was reduced to 10.0±9.5% (-5.2%, p=0.005). Target volume coverage represented by conformity and homogeneity indices could be improved by weekly plan adaptation (CI: p=0.007, HI: p=0.114) and reached levels of the initial plan (CI: p=0.721, HI: p=0.333). Conclusion: IGRT with CB-CT detects continuous GTV and PTV changes. CB-CT-guided ART for locally advanced NSCLC is feasible and enables superior sparing of healthy lung at high levels of plan conformity.